Time to surgery is not an oncological risk factor in patients with cholangiocarcinoma undergoing curative-intent liver surgery - Anna Mantas; Dong Liu; Carlos Constantin Otto; Lara Rosaline Heij; Daniel Heise; Philipp Bruners; Sven Arke Lang; Tom Florian Ulmer; Ulf Peter Neumann; Jan Bednarsch (Scientific Reports, 2024)
Abstract Surgical resection is the only option to achieve long-term survival in cholangiocellular carcinoma (CCA). Due to limitations of health care systems and unforeseeable events, e.g., the COVID pandemic, the time from diagnosis to surgery (time-to-surgery (TTS)) has gained great interest in malignancies. Thus, we investigated whether TTS is associated with the oncological outcome in patients who underwent surgery for CCA. A cohort of 276 patients undergoing curative-intent surgery for intrahepatic and perihilar CCA excluding individuals with neoadjuvant therapy and perioperative mortality between 2010 and 2021 were eligible for analysis. Patients were grouped according to TTS (≤ 30; 31–60; 61–90; > 90 days) and compared by Kruskal–Wallis-analysis. Survival was compared using Kaplan–Meier analysis and characteristics associated with cancer-specific survival (CSS), recurrence-free survival (RFS) and overall survival (OS) using Cox regressions. The median CSS was 39 months (3-year-CSS = 52%, 5-year-CSS = 42%) and the median RFS 20 months (3-year-CSS = 38%, 5-year-CSS = 33%). In univariable Cox regressions, TTS was not associated with CSS (p = 0.971) or RFS (p = 0.855), respectively. A grouped analysis with respect to TTS (≤ 30 days, n = 106; 31–60 days, n = 134; 61–90 days, n = 44; > 90 days, n = 29) displayed a median CSS of 38, 33, 51 and 41 months and median RFS of 17, 22, 28 and 20 months (p = 0.971 log rank; p = 0.520 log rank). No statistical difference regarding oncological risk factors were observed between the groups. This study is the first comprehensive analysis of TTS in CCA patients. Within a representative European cohort, TTS was not associated with earlier tumor recurrence or reduced CCS.